Effect of immunotherapy on overall survival in limited-stage small cell lung carcinoma: a national cancer database analysis - Bilani, Nadeem (Ther Adv Med Oncol, 2021)
BACKGROUND: While immune-based therapies have been approved for extensive-stage small cell lung cancer, there is limited data on the efficacy of immunotherapy in patients with limited-stage disease. METHODS: We used the National Cancer Database to first evaluate factors associated with the inclusion of immunotherapy as part of the initial therapeutic course in patients diagnosed with limited-stage small cell lung cancer (LS-SCLC). Consequently, we evaluated the impact of this immunotherapy on 2-year and 5-year overall survival (OS). We did this by performing 1:1 matching for controls that did not receive immunotherapy, and comparing survival between cohorts using the Kaplan–Meier method. RESULTS: A total of 98 patients with LS-SCLC received immunotherapy as part of their initial therapeutic regimen. Age and facility type were the only significant predictors of the use of immunotherapy. There was no statistically significant difference between matched case-control cohorts in median OS (p = 0.985), 2-year OS (p = 0.747), and 5-year OS (p = 0.934). CONCLUSION: In this study using a large national database, we found that the inclusion of immunotherapy as part of the initial systemic therapy regimen was not significantly associated with improved OS in a cohort of LS-SCLC patients.